Elucidation on the effect of operating temperature to the transport properties of polymeric membrane using molecular simulation tool - Lock, S.S.M. (Springer Verlag, 2017)
Existing reports of gas transport properties within polymeric membrane as a direct consequence of operating temperature are in a small number and have arrived in diverging conclusion. The scarcity has been associated to challenges in fabricating defect free membranes and empirical investigations of gas permeation performance at the laboratory scale that are often time consuming and costly. Molecular simulation has been proposed as a feasible alternative of experimentally studied materials to provide insights into gas transport characteristic. Hence, a sequence of molecular modelling procedures has been proposed to simulate polymeric membranes at varying operating temperatures in order to elucidate its effect to gas transport behaviour. The simulation model has been validated with experimental data through satisfactory agreement. Solubility has shown a decrement in value when increased in temperature (an average factor of 1.78), while the opposite has been observed for gas diffusivity (an average factor of 1.32) when the temperature is increased from 298.15Â K to 323.15Â K. In addition, it is found that permeability decreases by 1.36 times as the temperature is increased. © Springer Nature Singapore Pte Ltd. 2017.